ANÁLISE DE SEQUÊNCIA ALTERNATIVA PARA RESTAURAÇÃO LAMINADA:CIMENTO DE IONÔMERO DE VIDRO E RESINA COMPOSTA - Queiroz, Vania Aparecida Oliveira (2012)
Evaluate an alternative sequence for the sandwich technique using the microtensile bond strength testing on glass-ionomer cement (GIC)-dentin and GICcomposite resin (CR) interfaces (in 7 days), and to analyze the mechanical properties (hardness and modulus of elasticity) of GIC-RC interface (in 7 days and 24 months), by the use of nano-indentation. Methods: For that, class I cavities were cut into 60 extracted human molars. The cavities were filled using two diferent sequences of closed sandwich technique with conventional glass-ionomer cement (CGIC) (KetacTM Fil Plus/3M), and resin-modified glass-ionomer cement (RMGIC) (VitrebondTM/3M).The sequences were called, convencional sequence (CS) (etching GICs surface) and alternative sequence (AS) (without etching GICs surface), and they were used in all groups RMGIC-CR, RMGIC-dentin, CGIC-CR, and CGIC-dentin. After storage period, the teeth were horizontally sectioned, along vestibular wall of the class I cavities, for the bond strength of GICs-dentin tests. For analysis of the mechanical properties and bond strength of GICs-CR, the teeth were longitudinally sectioned.The specimens intended for mechanical properties testing have been removed from the sandwich restorations center areas. For the adhesion tests, the beams were aligned, and attached to a jig employing the active gripping method and stressed in tension (MPa). For the mechanical test, the specimens were embedded, and polished, and submitted to nano-indentation (GPa). The data were analyzed by Kruskal-Wallis, Dunn, and Chi-square tests (p<0.05). Results: The GICRM presented better adhesion to dentin and CR, and the CGIC presented better mechanical properties. When was used the RMGIC, both sequences did not present differences in adhesion (dentin and CR), and in mechanical properties (RMGIC,interface, and CR) in 7 days and 24 months. Concerning CGIC-dentin and CGIC-CR,also did not find a significant difference between both sequences, despite the adhesion means difference CGIC-CR between the CS (0.96 MPa) and AS (5.78 MPa). The CS presented a significant number of spontaneously debonded beams at interface with the CR before testing (77.33%) than AS (16%). The mechanical properties analysis of CGIC-interface-CR, in 7 days and 24 months, showed significant differences between techniques. At seven days, no GICC-RC interface data was obtained due to deteriorating condition, while AS showed 0.42 GPa (hardness) and 7.50 GPa (modulus of elasticity) values. After 24 months, AS showed hardness and modulus of elasticity, respectively, 1.24 e 20.96 GPa (CGIC), and 0.40 e 7.05 GPa (interface), while CS showed 0.51 e 8.14 GPa (CGIC) without any interface value. Conclusion: The AS has performed a good option for laminate or sandwich technique when RMGIC was used, and it was the best option when a CGIC was used.